Action and intent as behavior are part of human freedom. A brief look at using communication for social change from the point of view of Hannah Arendt: Una mirada a la comunicación para el cambio social desde el pensamiento de Hannah Arendt - Navarro Díaz, Luis Ricardo (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
After a brief tour of the central concepts of thought of Hannah Arendt, such as behavior, subject, pluralist attitude, public scope and freedom, the article suggests a theoretical discussion which sets as ground social change as a political agenda of human behavior. The settings which lead to such concepts of thought would require the participation and acknowledgement of others.